Characterization of high hydrostatic pressure-injured Bacillus subtilis cells*. Issue 6 (3rd June 2017) - Inaoka, Takashi; Kimura, Keitarou; Morimatsu, Kazuya; Yamamoto, Kazutaka
Abstract : High hydrostatic pressure (HHP) affects various cellular processes. Using a sporulation-deficient Bacillus subtilis strain, we characterized the properties of vegetative cells subjected to HHP. When stationary-phase cells were exposed to 250 MPa of HHP for 10 min at 25 °C, approximately 50% of cells were viable, although they exhibited a prolonged growth lag. The HHP-injured cells autolyzed in the presence of NaCl or KCl (at concentrations ≥100 mM). Superoxide dismutase slightly protected the viability of HHP-treated cells, whereas vegetative catalases had no effect. Thus, unlike HHP-injured Escherichia coli, oxidative stress only slightly affected vegetative B. subtilis subjected to HHP. Graphical abstract: Cell death and the recovery of HHP-injured Bacillus subtilis vegetative cell.